2016
DOI: 10.3389/fnsys.2016.00068
|View full text |Cite
|
Sign up to set email alerts
|

Off to a Good Start: The Early Development of the Neural Substrates Underlying Visual Working Memory

Abstract: Current neuroscientific models describe the functional neural architecture of visual working memory (VWM) as an interaction of the frontal-parietal control network and more posterior areas in the ventral visual stream (Jonides et al., 2008; D'Esposito and Postle, 2015; Eriksson et al., 2015). These models are primarily based on adult neuroimaging studies. However, VWM undergoes significant development in infancy and early childhood, and the goal of this mini-review is to examine how recent findings from neuros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…3 et al, 2010). Several studies accentuated the crucial roles of attention (Posner et al, 2016), working memory (Fitch et al, 2016), and speed of processing (Horowitz-Kraus et al, 2017a) as early as in infancy. These studies provided foundational evidence for EF training in early childhood (Diamond and Lee, 2011;Rueda et al, 2005Rueda et al, , 2012Wardhana, 2016), which corresponds to the Anderson model for the development of EF (Anderson, 2002).…”
Section: Providing Neurobiological Evidence For the Anderson Ef Modelmentioning
confidence: 99%
“…3 et al, 2010). Several studies accentuated the crucial roles of attention (Posner et al, 2016), working memory (Fitch et al, 2016), and speed of processing (Horowitz-Kraus et al, 2017a) as early as in infancy. These studies provided foundational evidence for EF training in early childhood (Diamond and Lee, 2011;Rueda et al, 2005Rueda et al, , 2012Wardhana, 2016), which corresponds to the Anderson model for the development of EF (Anderson, 2002).…”
Section: Providing Neurobiological Evidence For the Anderson Ef Modelmentioning
confidence: 99%
“…In humans, the development of early functional connections between the thalamus and the salience network (anterior cingulate, insula and caudate nucleus) is correlated with greater spatial working memory ability at 2 years old (Alcauter and others 2014). Electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) studies of very young infants suggest the developing frontoparietal network may also contribute, albeit to a lesser degree, to early working memory function (Fitch and others 2016), indicating that development of the working memory system may entail quantitative, rather than qualitative changes to the regions involved in working memory.…”
Section: Working Memory Throughout the Life Spanmentioning
confidence: 99%
“…VWM is a cognitive system that is used roughly 10,000 times per day for at least two kinds of work-comparison of percepts that cannot be viewed at the same time and detecting changes in the world when they occur (Vogel & Luck, 1997;Vogel, Woodman, & Luck, 2001). Behavioural studies have shown that the development of VWM begins in infancy and gradually improves throughout childhood and adolescence (Fitch, Smith, Guillory, & Kaldy, 2016). Due to its early emergence and the availability of tasks that can be used in infancy to predict later achievement (Rose, Feldman, & Jankowski, 2012), VWM is an excellent marker of early cognitive development.…”
mentioning
confidence: 99%